Design and application of an indwelling urinary catheter with the function of preventing traction injury caused by unplanned removal of catheter (一种防止拉扯损伤的留置导尿管的设计与应用) - CAO Zhangkun (曹张坤); LI Hui (李慧); WANG Youxia (王有霞) (中西医结合护理)
Given the severity of illness conditions, most ICU patients require placement of indwelling urinary catheters for a long time. In order to enhance patient safety during catheter retention, reduce urethral injury and bleeding caused by unplanned catheter removal, and lower catheter-associated urinary tract infections, this paper introduces the design and application of a indwelling urinary catheter with the function of preventing traction injury. The aim is to effectively reduce urethral injury during unplanned catheter removal, decrease the risk oif urethral bleeding and pain, and lower the incidence of catheter-associated urinary tract infections. (危重症患者因自身病情特点及治疗需求, 需长期留置导尿管。为提升尿管留置期间患者的安全水平, 降低因非计划拔管引发的尿道损伤出血以及减少导尿管相关尿路感染风险, 需要深入探究留置尿管的材质特性、功能设计等因素。本文介绍一种实用新型防止拉扯损伤的留置导尿管的设计和使用方法, 能有效避免非计划性拔管造成尿道损伤, 提高患者置管安全性。)